Generative AI in East Asian Newsrooms: Adoption, Anxiety, and Editorial Gatekeeping in Korea, Japan, and Taiwan - Moon, Hye-Jin; Yamamoto, Sota (Journal of Contemporary Eastern Asia, 2026)
Drawing on 62 interviews with journalists and editors in Seoul, Tokyo, and Taipei, this study compares newsroom adoption of generative AI tools. We identify three gatekeeping regimes — experimental, contained, and prohibited — and link them to organizational ownership structures and national AI governance debates.
Keywords: generative AI; journalism; East Asia; newsrooms; gatekeeping